Retrospective Analysid Of Outcomes After Different Surgical Approaches For Tha - Prakash, Ankit; Gautam, Ajinkya; Prabhat, Prabhat; Prasad, Mahesh (Journal of Neonatal Surgery, 2025)
Background: Total Hip Arthroplasty (THA) is a widely performed orthopedic procedure aimed at alleviating pain and restoring mobility in patients with hip joint disorders such as osteoarthritis, rheumatoid arthritis, and avascular necrosis. Among the various surgical approaches, the posterior, direct anterior, and lateral techniques are most commonly employed. Each approach presents unique benefits and limitations in terms of surgical access, complication rates, functional recovery, and postoperative rehabilitation. This study aims to compare the outcomes associated with these three approaches in a single-center, retrospective setting. Methods: A retrospective observational study was conducted from March 2023 to September 2024, including 50 patients who underwent primary THA. Patients were grouped based on the surgical approach used: posterior (n = 20), direct anterior (n = 15), and lateral (n = 15). Data collected included demographic details, operative time, blood loss, pain scores (VAS), functional outcome (Harris Hip Score at 6 months), complication rates, and length of hospital stay. Statistical analysis was performed using SPSS software, with a p-value < 0.05 considered significant. Results: The direct anterior approach demonstrated the most favorable outcomes, with the lowest VAS pain scores (1.8), highest Harris Hip Scores (91.5), and shortest hospital stay (3.8 days). The posterior approach had the shortest operative time (76 minutes) but was associated with two cases of dislocation. The lateral approach yielded intermediate outcomes, with no dislocations reported. One case of temporary nerve symptoms was noted in the anterior group. Conclusion: While all three approaches significantly improved pain and function, the direct anterior approach offered superior early outcomes. However, surgical approach selection should be individualized based on patient anatomy, comorbidities, and surgeon experience. Further prospective studies are needed to confirm these findings.